Rational creation of chiral multinuclear and metallosupramolecular compounds from thiol-containing amino acids - Igashira-Kamiyama, Asako; Konno, Takumi (Dalton transactions : an international journal of inorganic chemistry, 2011)
Developments in the rational creation of chiral multinuclear and metallosupramolecular compounds based on linear-type metal complexes with penicillaminate (pen), as well as their functionality as a multidentate chiral metalloligand, is the main subject of this paper. The reactions of a mononuclear Au(I) complex, [Au(d-pen)(2)](3-), in which two d-pen ligands bind to an Au(I) center through thiolato S atoms, with transition metal ions afford a variety of S-bridged heterobimetallic multinuclear complexes, the structures and properties of which are highly dependent on the nature of reacting metal ions. The created multinuclear complexes still act as a metalloligand when they possess free amine and/or carboxylate groups, leading to the formation of heterotrimetallic supramolecular structures by reacting with third metal ions. While the Au-S bonds in [Au(d-pen)(2)](3-) are generally retained in the course of the reactions with metal ions, this is not the case for the Hg-S bonds in the corresponding Hg(II) complex, [Hg(d-pen)(2)](2-). A remarkable chiral behavior of multinuclear complexes composed of [Au(l-cys)(2)](3-) (cys = cysteinate), which is opposite to that composed of [Au(l-pen)(2)](3-), is also presented.